THE EFFECT OF POLYETHYLENE GLYCOL (PEG) 6000 ON GREEN MUSTARD (Brassica juncea L.) GERMINATION AND GROWTH - Garri Abdi Nusantara; Tundjung T. Handayani; Zulkifli Zulkifli; Sri Wahyuningsih (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
The frequent drought in Indonesia has caused many farmers to experience a decline in vegetable production, one of which is green mustard. The green mustard is not resistant to drought, so water supply is an aspect that must be given special attention in cultivating green mustard. The objective of this study was to know whether the seedling and growth of seedling of green mustard (Brassica juncea L.) can grow well under drought stress by Polyethylene glycol 6000. This study was conducted in the Laboratory of Plant Physiology, Department of Biology, Faculty of Mathematics and Natural Science, the University of Lampung in 2019. This study was conducted in a Completely Randomized Design with the main factor is Polyethylene glycol 6000 with three levels: 0% w/v, 10% w/v, 20% w/v, and 30% w/v. Each combination of treatments was repeated five times. The number of the experimental unit was 20. The observed variables in this study were the percentage of seed germination, length of leaf, the width of leaf, a,b chlorophyll content, and total chlorophyll content. The data was homogenize using the Levene test, then continued to analyze using ANOVA at a 5% significant level and proceed with HSD test significant level 5% to determine the differences between the treatment. The result showed that under drought stress by Polyethylene glycol 6000 started to affect green mustard seedling and growth of seedling at the level of PEG 6000 concentration 20% w/v while the number of leaves not affected. The conclusion was PEG 6000 gave a negative impact on the green mustard and the green mustard induced by PEG 6000 10% w/v more adaptive than PEG 6000 20 w/v.